Meningkatkan Literasi AI dan Kesadaran Etika Digital melalui Edukasi Interaktif bagi Pelajar Sekolah Menengah Atas - Pungus, Stenly Richard; Sondakh, Debby Erce; Liem, Andrew Tanny; Adam, Stenly Ibrahim; Mambu, Joe Yuan Yulian; Tombeng, Marchel Timothy (Universitas Klabat, 2025)
This Community Service Program was conducted at SMA Negeri 2 Kota Bitung with the aim of enhancing students’ literacy on the basic concepts of Artificial Intelligence (AI), while also fostering awareness regarding ethical and privacy issues in the use of AI-driven technologies in educational settings. The approach employed was an interactive workshop consisting of AI introduction, discussions on digital ethics and privacy, and practical training in designing effective and responsible AI prompts. A total of 27 eleventh-grade students from various academic tracks actively participated in this program. The results of pre-tests and post-tests indicated a significant improvement in students’ understanding of how AI works and its ethical implications. Furthermore, students demonstrated high enthusiasm in crafting contextually relevant prompts for learning purposes. This initiative shows that integrating AI education with a contextual and reflective learning approach can be an effective strategy to develop a generation of students who are not only technologically literate but also ethically conscious in their digital behavior. The program is recommended for replication in other schools as part of a broader effort to strengthen national digital literacy